Development of Creativity and Innovation in Guidance and Counseling: A Sufistic Approach - Muhamad Rifa'i Subhi; Burhan Yusuf Habibi (Pamomong: Journal of Islamic Educational Counseling, 2022)
This research aims to obtain an alternative paradigm in the development of creativity and innovation guidance and counseling based on the sufistic approach. To this end, a qualitative approach was applied. The content analysis technique comprising open coding, axial coding, and selective coding was applied. The open coding stage was used to identify, classify, and decompile important data. In the axial coding stage, findings from the open coding stage were linked to broader categories to obtain better picture. The selective coding stage was used as the process of selecting core categories and developing them into more systematic concepts by integrating all findings. The results showed that spirituality is a potential ability that exists in individuals. This ability is manifested in the practice of worship as a form of servitude to Allah. The worshipping experience can be utilized as a therapeutic process in guidance and counseling. Some of the practices of worship included salat, reading al-Qur’an, zakat, dzikr, salawat, and shukr.